2018
DOI: 10.18549/pharmpract.2018.03.1268
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in hospitals: patients’ satisfaction and related barriers

Abstract: Background:Suboptimal pain control has been frequently reported in healthcare settings and documented to negatively impact patients’ health. Patients’ perception regarding pain management may influence their satisfaction regarding treatment.Objectives:This study focuses on the assessment of patients’ satisfaction regarding pain therapy and defining patient-related barriers for its implication.Methods:A cross-sectional study was conducted in two tertiary care hospitals from April till July 2017. A face-to face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…18,26 Similarly, Tawil et el provided optimistic data that 84.7% of the patients were either satisfied or strongly satisfied. 27 This finding was also in line with recently published research on pain in Vietnam, which indicated that 58.97% of respondents were either satisfied or extremely satisfied with their pain control. 7 However, the previous study did not provide specific aspects of patient satisfaction with pain management and did not focus on the older age population.…”
Section: Discussionsupporting
confidence: 87%
“…18,26 Similarly, Tawil et el provided optimistic data that 84.7% of the patients were either satisfied or strongly satisfied. 27 This finding was also in line with recently published research on pain in Vietnam, which indicated that 58.97% of respondents were either satisfied or extremely satisfied with their pain control. 7 However, the previous study did not provide specific aspects of patient satisfaction with pain management and did not focus on the older age population.…”
Section: Discussionsupporting
confidence: 87%
“…These results were consistent with another study, where only a few patients reported that nurses taken additional actions to manage their pain. [ 16 ] Non-pharmacological therapies alone are not efficacious for the treatment of acute postoperative pain but they may act as good adjunct. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Patients are satisfied even though they suffer from moderate-to-severe pain and had to wait for a relatively longer time for pain medication. [ 16 ] This issue could only be handled through patient education for adequate reporting the postoperative pain and active patient participation in pain management.…”
Section: Discussionmentioning
confidence: 99%
“…In this project, it was shown that 84.7% of pain patients were satisfied or very satisfied with the care, which is explained by the fact that only 7.7% of patients had to wait more than 30 minutes before receiving pain medication on demand and only 10.9% of them did not receive any additional pain medication for their growing pain. In addition, almost half of the study participants received sufficient education in the field of pain and therapy [43]. Such beneficial practices related to patient involvement in the care process could explain the high patient satisfaction results, despite the significant functional consequences of pain experienced.…”
Section: Implications For Nursing Practicementioning
confidence: 99%